Why rare diseases? - Giuseppe Remuzzi; Arrigo Schieppati (Istituto Superiore di Sanità, 2011)
Patients with rare diseases are awaiting an answer to their needs. Traditionally, however, research on rare diseases has been limited by the idea that it was too difficult to do and too little rewarding in terms of return of profit. This attitude has actually changed during the last decade, because it was realized that research on rare diseases may help finding solutions valid also for common conditions. Indeed, while we all invoke translational research as the way to adapt results of laboratory studies into therapeutic interventions for patients, rare diseases often need the opposite path: we observe rare patients in the clinical practice, then we find out that they have a genetic defect, and finally we reproduce the defect in an animal model to extend the observation further beyond the clinic. In the process we also learn a lot about the physiology and the pathology and have insight into the mechanisms of common diseases. In other words, studying a rare condition may enlighten the path to other discoveries and to break the boundaries between disciplines and specialities to provide solutions for the sake of the patients.